The Impact of Physical Screening on Position Selection and Performance in Smash Badminton Athletes - A Literature Review - Nimrot Manalu (Ikatan Sarjana Olahraga Republik Indonesia (Kabupaten Kampar), 2025)
Objectives: To systematically evaluate the relationship between physical screening assessments and their impact on position selection and smash performance in competitive badminton players. Methods: A comprehensive literature review was conducted across electronic databases including PubMed, SCOPUS, Web of Science, and sport-specific databases from January 2000 to March 2025. Search terms included combinations of